(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aimed to examine the impact of digital transformation on the development of administrative services in Libya, through an applied study conducted at the University of Zawiya. The study adopted a descriptive-analytical approach, which focuses on describing the phenomenon, analyzing it, and interpreting the relationships between its variables. The study population consisted of administrative employees at the university, from which a simple random sample of 80 employees was selected. A questionnaire was used as the primary data collection tool, comprising two main dimensions: digital transformation and administrative services. Data were analyzed using both descriptive and inferential statistical methods, including mean, standard deviation, and percentages, as well as Pearson correlation, linear regression analysis, and the independent samples T-test. The findings revealed a moderate to high level of digital transformation implementation within the institution. The results also indicated a clear improvement in the quality of administrative services, particularly in transaction processing speed and procedural accuracy. Furthermore, a strong positive and statistically significant relationship was found between digital transformation and the development of administrative services, with digital transformation explaining a considerable proportion of the variance in service quality. The study also identified several obstacles limiting the effectiveness of digital transformation, most notably weak technical infrastructure, the need for continuous training, and resistance to change among some employees.